Biomechanical comparison of cutting techniques: A review and practical applications - dos Santos, T.; McBurnie, A.; Thomas, C.; Comfort, P.; Jones, P. A. (Strength and Conditioning Journal, 2019)
Cutting actions are important maneuvers in multidirectional sport and are also key actions associated with noncontact anterior cruciate ligament injury; however, it is important to note that 3 primary cutting techniques have been studied within the literature: the side-step, crossover cut, and split-step. These cutting techniques demonstrate kinetic and kinematic differences, which have distinct implications for both performance and potential injury risk. In this review, we discuss the advantages and disadvantages of the 3 cutting techniques and provide cutting technical guidelines, verbal coaching cues, and change-of-direction speed and agility programming recommendations to enhance performance and promote safer mechanics.